Feindbild Moslem
This broadcast focuses on the position of Muslims in Croatia, particularly the 200.000 Bosnian refugees. Croatia propaganda has portrayed Muslim fundamentalism a danger to the Christian world. This report includes numerous interviews with Croats and Muslims giving their opinions on the status of Muslim refugees. The first unidentified Muslim man states that Muslim men are commonly arrested and taken to camps. Many Muslims have also lost their homes and their jobs, he points out. The second unidentified Muslim man talks about being fired without an explanation from a Croat firm he worked for. An unidentified Muslim woman states that Muslims are constantly being kicked around and that Croats want them out of their country. A young Croat man states that it is not fair for Croatia to be spending millions of dollars on taking care of the Bosnian Muslim refugees when Croats themselves are experiencing economic hardship. An older Croat man explains that Muslims are taking away Croat territory in Bosnia; hence, they should not be helped. A Muslim refugee talks about the open repression where Muslim civilian men are being used for exchange for Croat war prisoners. Aziz Mikic, leader of the Croat Muslim Party talks about the mistake made by Izetbegovic in trying to make an Islamic republic in Europe. Dr. Sefko Omerbasic explains that the Bosnian army does include some fundamentalists and that they have committed crimes as well, but that they are not religiously inspired, but only a reaction to the turmoil of the Bosnian war. Zagreb University Professor Zarko Puhovski explains that the general sentiment of Croats is that of being victimized. He states that Croatia feels like the West has forgot about it. An unidentified Croat woman talks about the morality of refusing help to a people. Other footage available in this report: Bosnian Muslims waiting in front of their consulate, a camp housing Muslim refugees, a mosque in Zagreb and men praying, a street salesman selling Croat nationalist paraphernalia, and general pictures of people in the streets of Zagreb.